Do investment and financing decisions impact the performance and value of Indonesian shipping companies?/ Rudy Kurniawan and Zuliani Dalimunthe - Kurniawan, Rudy; Dalimunthe, Zuliani (Universiti Teknologi Mara Selangor, 2022)
This paper analyses the impact of investment and financing decisions on the performance and value of Indonesian shipping companies. We use Economic Value Added (EVA) as the proxy to measure the company's performance and Tobin's Q (TOBIN-Q) to measure the company's value. This paper uses annual audited financial reports of all Indonesian shipping companies listed on the Indonesian Stock Exchange from the year 2016 to 2020. The data are analysed using panel data regression and the main findings are further confirmed through online interviews with three decision-makers from three listed Indonesian shipping companies. The statistical description shows that Indonesian shipping companies rely on bank loans as their primary financing source. We find that investment decisions, as measured with Fixed Asset Growth (FAG), have a significantly positive relationship with the company's performance and value. We also find a significantly negative relationship between the company's Weighted Average Cost of Capital (WACC) and its performance and value.